ON THE ISSUE OF METHODOLOGY OF ESTIMATING THE REGIONAL COMPETITIVE ADVANTAGES BY TYPES OF ACTIVITY - A. R. Safiullin (Russian Journal of Economics and Law)
Objective: to develop the research methodology of the competitive position of territories by types of economic activities, to define the relevant types of economic activities and to diagnose their competitive advantages. Methods: a differentiated approach to the analysis of competitiveness based on matrix models of competitive positioning, which allows to identify the relevant types of economic activities of the territory. This approach determined the choice of specific research methods: dialectics, abstraction, systematic, logical, structural, comparative, and statistical. The application of the above methods helped to ensure the validity of the analysis results, theoretical and practical conclusions. Results: in the study were used the experience and knowledge gained during an earlier undertaken series of projects relating to the assessment of economy efficiency of Tatarstan Republic in 2005-2011.Previous reports dealt with the change of the selected industries positions of the Republic, the structure and dynamics of the competitive position of these industries compared to the leading Russian regions. A distinctive feature of the research results presented in this article is a comparative analysis of competitive advantages of economic activities of Tatarstan Republic based on the matrix model of competitive positioning. Scientific novelty: for the first time, the matrix model of diagnostics of competitive advantages of the territory by the type of economic activity was proposed, which allows to identify the priority industrial portfolio and provide targeted management actions to enhance its investment attractiveness. Practical value: the main provisions and conclusions of the article can be used by legislative and executive authorities of the Russian Federation, business community, research institutions and organizations to develop strategies and programs of socio-economic development and territorial planning schemes, priority directions of industrial and investment policy, modernization and innovative growth scenarios.